(untitled) (Contemporary Journal of Social Science Review, 2025)
Pakistan’s political history has been marked by the judiciary’s support of military takeovers, which has had a significant impact on the stability and growth of the nation’s democracy. In the past, Pakistan’s Supreme Court has frequently used the theory of state necessity which defends extra-constitutional actions as required to maintain order and avert chaos to legitimize military takeovers. Beginning with the military takeover in 1958, this trend has persisted through later interventions, such as those headed by Generals Pervez Musharraf in 1999 and Zia-ul-Haq in 1977. In its historic decision supporting Musharraf’s coup in 2000, the Supreme Court not only upheld the military coup but also gave the military government the authority to change the constitution and rule during the transitional period without parliamentary control. The rule of law and democratic governance in Pakistan have been undermined by such court decisions, which have weakened civilian institutions, eroded constitutional supremacy, and strengthened military influence in politics. The judiciary has frequently given up its independence and constitutional mandate in order to maintain stability under military rule, which highlights the brittleness of Pakistan’s democracy. The judiciary has enabled a cycle of military interventions that undermine democratic continuity and marginalize elected governments by supporting these coups. Further polarizing the political landscape and eroding public trust in democratic institutions is the judiciary’s involvement in politically contentious cases, such as the disqualification of political leaders. A key element in maintaining authoritarianism and impeding the consolidation of democracy in Pakistan has been the judiciary’s compromised role, which is highlighted by the frequent pattern of judicial approval of military takeovers.